Evaluasi Kritis Hubungan antara Indonesia dan China-Tiongkok - Hamka Hamka; Sri Yunanto; Cecep Effendi (Journal on Education, 2024)
This study critically evaluates the relationship between Indonesia and China from 2014 to 2023, a period marked by significant geopolitical shifts and economic collaborations. The research examines the multifaceted nature of this bilateral relationship, encompassing economic partnerships, strategic challenges, and regional dynamics. Particular attention is given to China's Belt and Road Initiative and its impact on Indonesia, as well as the complexities surrounding territorial disputes in the South China Sea. The study highlights Indonesia's efforts to balance economic opportunities with national interests, emphasizing its careful diplomatic approach and strategic positioning in Southeast Asia. This analysis provides insights into the evolving nature of Indonesia-China relations and their implications for regional stability and Indonesia's long-term development prospects.